Implementation of Individual Counseling Services with a Cognitive Behavior Therapy Approach for Female Students with Moral Conditions - Nazlah Hidayati; Zahratul Wardah Bidaula (Interpersonal: Jurnal Bimbingan Konseling Islam, 2026)
Education in Islamic boarding schools is a comprehensive educational unit that encompasses all aspects of students' lives. Various pesantren have developed and implemented methods and strategies believed to optimize and maximize education in their institutions. One such institution is Al-Amien Prenduan Islamic Boarding School, which categorizes student graduation into three categories: positive graduation, conditional graduation (conditional on moral behavior and Quranic recitation), and failure to graduate. To optimize guidance for female students with conditional moral behavior, individual counseling services with a Cognitive Behavior Therapy (CBT) approach are provided. This study aims to discuss the implementation and results of CBT as a counseling guidance method for a fenale students with conditional moral behavior who experiences cognitive distortion, namely the assumption that she is difficult to change and useless, as well as the thought that she is considered insignificant and viewed negatively by others, which affects her performance as a manager. The research method used is qualitative field research in the form of a case study, with data collection techniques including observation, interviews, and documentation. The implementation of individual counseling services with a CBT approach for female students with conditional moral behavior is carried out in three counseling stages: preparation, implementation, and final stages, and is conducted in five meeting sessions, which include four core stages: assessment, goal setting, technique implementation, evaluation, and termination. The results show that the counselee becomes more confident, performs tasks well, and is able to control her emotions. This study is expected to serve as a reference source for addressing similar problems and as one of the efforts to improve the counseling process in Iskamic Boarding School.